Daniel Forthomme, optometrist, professor, researcher, director and friend (1938-2019) - Gresset, Jacques; Giasson, Claude; Simonet, Pierre (Canadian Journal of Optometry, 2020)
Daniel Forthomme had a profound influence on many of us and on our profession. Throughout his long career as an optometrist, professor, di-rector of the School of Optometry and of Optométristes Sans Frontières, he adapted to change, always giving his best; hence his remarkable influence on all Quebec op-tometrists and on our profession.